Neuroinflammation: The Abused Concept - Elena Galea; Manuel B. Graeber (ASN Neuro, 2023)
Scientific progress requires the relentless correction of errors and refinement of hypotheses. Clarity of terminology is essential for clarity of thought and proper experimental interrogation of nature. Therefore, the application of the same scientific term to different and even conflicting phenomena and concepts is not useful and must be corrected. Such abuse of terminology has happened and is still increasing in the case of “neuroinflammation,” a term that until the 1990s meant classical inflammation affecting the central nervous system (CNS) and thereon was progressively used to mostly denote microglia activation. The resulting confusion is very wasteful and detrimental not only for scientists but also for patients, given the numerous failed clinical trials in acute and chronic CNS diseases over the last decade with “anti-inflammatory” drugs. Despite this failure, reassessments of the “neuroinflammation” concept are rare, especially considering the number of articles still using the term. This undesirable situation motivates this article. We review the origins and evolution of the term “neuroinflammation,” discuss the unique tissue defense and repair strategies in the CNS, define CNS immunity, and emphasize the notion of gliopathies to help readdress, if not bury, the term “neuroinflammation” as it stands in the way of scientific progress.